Necrotizing Parasagittal Meningioma in Patient with Systemic Lupus Erythematosus after Treatments with Methotrexate and Hydroxychloroquine - Wangapakul, Thitikan; Moguel, Ambar Elizabeth Riley; Kayssi, Abdel Raouf (Journal of Neurological Surgery Reports, 2024)
Objective Meningiomas are the most common extra-axial tumors of the central nervous system. Meningiomas are particularly problematic when they invade deep or vital structures, causing the tumors to be inoperable. Nonsurgical adjunctive or salvage treatments to shrink a meningioma with multiple recurrences, located in deep-seated area or surgically unfit area, remain underexplored. The authors report a rare case of a spontaneously necrotic meningioma (World Health Organization [WHO] grade I) in a patient with systemic lupus erythematosus on chronic methotrexate and hydroxychloroquine.Case Study A 29-year-old female with systemic lupus erythematosus had been treated with methotrexate and hydroxychloroquine for 7 years. She presented with episodes of seizures and hemiparesis. Neuroimaging revealed a possible necrotic meningioma in the left parietal parasagittal area. Subsequent intraoperative findings showed lytic tissue of the tumor, and by histopathology results the tumor was classified as WHO grade I with massive necrosis. After craniotomy with tumor removal, the patient's motor function fully recovered without recurrent seizures.Discussions Necrotizing of small and benign meningioma is rarely found but otherwise interesting. The cause of this phenomenon is not yet understood thoroughly. In this case, we suspected various possible causes such as vasculitis interrupting blood supply, use of immunosuppressive drugs such as hydroxychloroquine or methotrexate, or, less likely, latent infections in the immunocompromised patient. Despite the lack of more evidence supports, this finding encourages further study of nonsurgical or salvage treatment of inoperable meningioma, so sequalae after refractory recurrences of meningioma can be prevented, and patient treatment outcomes can be improved.
Keywords: necrotic meningioma; salvage treatment; hydroxychloroquine; methotrexate; nonsurgical treatments; systemic lupus erythematosus